Qualitative research and thematic content analysis. Intellectual orientation of Universum journal - Díaz Herrera, Claudio (Revista General de Información y Documentación, 2018)
Responding to a technical and methodical problem that allows to identify some thematic or intellectual orientation in a means of academic dissemination, the article proposes a theoretical-methodological support, which contributes towards the procedural elaboration of an analysis of thematic and qualitative content for these investigative purposes. The proposal can be applied in studies where it is feasible to constitute an information trajectory longitudinally, expressed in scientific production format, as periodical journals, conference proceedings, library catalogs, etc. The foregoing, to the extent that there is multidisciplinary wealth or a certain thematic diversity contained in these media. In empirical terms, the theoretical-methodological proposal was applied in the Universum journal, that after 30 years of editing, its genesis is characterized by a miscellaneous composition, determining a transit through diverse thematic of study until being indexed scientifically, fact that led to his affiliation to the humanities and social sciences area. The proposal becomes a valid procedure to constitute the thematic orientation of a journal. In light of the results, it is concluded that Universum is predominantly oriented towards four central labels, first a dimension of humanism and letters; secondly, a dimension of social, political and cultural theory; continuing with a dimension in economic development and administration; to end with history of ideas. Finally, the qualitative procedures applied, contribute technically to the construction of labels / dimensions, which once systematized, categorized and re-categorized, give an account of a thematic orientation in this diffusion medium.